2018
DOI: 10.1080/20008198.2018.1506230
|View full text |Cite
|
Sign up to set email alerts
|

What aspects of post-traumatic growth are experienced by bereaved parents? A systematic review

Abstract: Background: The death of a child of any age can be traumatic and can leave bereaved parents experiencing negative psychological outcomes. Recent research has shown the potential utility for understanding more about the development of post-traumatic growth following bereavement.Objective: This paper sought to identify the aspects of post-traumatic growth experienced by bereaved parents and the factors that may be involved in facilitating or preventing post-traumatic growth.Methods: A systematic search of peer-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 34 publications
1
25
0
1
Order By: Relevance
“…Reports of PTG have been documented among survivors of various types of traumatic events. These include combat or other military-related traumatic events ( Mark et al, 2018 ; Stein et al, 2020 ; Zerach, 2020 ), natural and manmade disasters (S. Brooks et al, 2020 ; Palgi et al, 2020 ), accidents, life-threatening physical illnesses ( Hefferon et al, 2009 ), bereavement ( Waugh et al, 2018 ), and childhood abuse ( Kaye-Tzadok and Davidson-Arad, 2016 ; Lev-Wiesel et al, 2004 ; Shakespeare-Finch and De Dassel, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reports of PTG have been documented among survivors of various types of traumatic events. These include combat or other military-related traumatic events ( Mark et al, 2018 ; Stein et al, 2020 ; Zerach, 2020 ), natural and manmade disasters (S. Brooks et al, 2020 ; Palgi et al, 2020 ), accidents, life-threatening physical illnesses ( Hefferon et al, 2009 ), bereavement ( Waugh et al, 2018 ), and childhood abuse ( Kaye-Tzadok and Davidson-Arad, 2016 ; Lev-Wiesel et al, 2004 ; Shakespeare-Finch and De Dassel, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, their average time since the loss was 8.30 years, but which was limited to 2 years in the other two studies. Time since the loss seems to be an important factor associated with PTG ( Waugh et al, 2018 ). A study on bereaved youth also did not find this curve relationship ( Salloum et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Model 1 was used to explore the moderating role of interpersonal loss, while Model 2 for socio-economic loss. A systematic review of bereaved parents’ PTG suggested that gender, time since the death, and cause of death may impact PTG ( Waugh et al, 2018 ), and the continuation of family lineage is important in China. Therefore, the gender of participants (0 = male and 1 = female), time since the loss (years), cause of death (0 = non-violent, such as chronic disease; 1 = violent, such as an accident), and having a grandchild or not (0 = no and 1 = yes) were entered as covariates in step 1; grief was entered in step 2; squared grief levels (grief 2 ) was entered in step 3 to assess the curvilinear relationship between grief and PTG.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations